সত্য মামলা আগরতলা - আলী, শওকত, ১৯৩৭- (ঢাকা : প্রথমা প্রকাশনা, 2011)
Autobiographical reminiscences of an army official about Sheikh Mujibur Rahman, 1922-1975, first president of Bangladesh and his involvement in a political conspiracy case, conducted in 1968.
In Bengali.
Donated By Akbar Ali Khan
Keywords: Mujibur Rahman, -- Sheikh, -- 1922-1975 -- Trials, litigation, etc; Ālī, Śaokata, -- 1937- -- Trials, litigation, etc; Trials (Conspiracy) -- Bangladesh; Bangladesh -- Politics and government